Influence Factor Analysis of Consumer Decision in Using Special Tariff Policy on Regional Rail in Indonesia (Case Study : Sawunggalih Regional Train) - Baldat, Agil Gian; Septiani, Isse Liana; Andriansyah, Yuda; Sugiyanto, Martinus Agus; Hariani, Mira Lestira (Al-Makki Publisher, 2024)
Indonesian railway transportation service companies are constantly striving to improve service and facility optimization while increasing train passenger numbers. The purpose of this study is to examine the impact of special fare tickets on train user decisions in order to boost passenger traffic and strengthen railways' role in the regional economy. This study examines price, time (length), and certainty opportunities as influences on the decision to acquire special fare tickets for public transportation trains. The study took a quantitative approach, with the questionnaire asking about Ability to Pay (ATP) and Willingness to Pay (WTP). Furthermore, the data was examined using multiple linear regressions to identify the impact of variables on consumer behavior. Overall, 54% of respondents can buy rail tickets at official pricing, including regular and special fares. 44% of respondents always purchase special price train tickets for long journeys and always take trains. Therefore, the resulting regression model is as follows: Y=3.115 - 0.49X1 + 0.042X2. The price variable shows a negative influence (-0.49), indicating that the greater the ticket price, the less likely someone will purchase a special fare train ticket. In contrast, the time variable has a positive effect, with a value of + 0.043, indicating that the longer the time given, the more likely someone will opt to buy.